2005
DOI: 10.1007/s10038-005-0259-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetics analysis with whole chromosome paint probes of sperm nuclei from a (13;15) Robertsonian translocation carrier

Abstract: Meiotic segregation of a Robertsonian translocation (13;15) was assessed in sperm nuclei using dualcolor fluorescent in situ hybridization (FISH) with whole-chromosome paint probes. Most spermatozoa in the (13;15) translocation carrier resulted from alternate segregation. Although an increased frequency of unbalanced gametes was observed, spontaneous pregnancy led to the birth of a boy with a normal karyotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…Male carriers usually have oligozoospermia (3)(4)(5)(6)(7)(8)(9)(10)(11), and intracytoplasmic sperm injection is suggested to be applied, whereas the clinical manifestations of the female carriers are usually repeated abortions, malformation, or death fetuses. Munn e's (17) study indicated that there was no difference between male and female chromosome abnormalities in embryos of RTs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Male carriers usually have oligozoospermia (3)(4)(5)(6)(7)(8)(9)(10)(11), and intracytoplasmic sperm injection is suggested to be applied, whereas the clinical manifestations of the female carriers are usually repeated abortions, malformation, or death fetuses. Munn e's (17) study indicated that there was no difference between male and female chromosome abnormalities in embryos of RTs.…”
Section: Discussionmentioning
confidence: 99%
“…Carriers of RTs are usually phenotypically normal; nevertheless, they suffer from more frequent fertility problems, such as oligozoospermia or recurrent spontaneous abortion (3)(4)(5)(6)(7)(8)(9)(10)(11). Theoretically, a RT carrier has six different karyotype gametes.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…During the last decade, meiotic segregation in spermatozoa has been repeatedly studied in male carriers of Rob translocations [2][3][4][5][6][7][8][9][10][11][12]. Most of these studies showed strong prevalence of alternate segregation in gametes.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the FISH‐analysis does not allow determination of the actual relationship between the two cell lines in semen. However, previous studies of spermatozoa from dic(13;15) translocation carriers have shown disomy 13 and nullisomy 13 spermatozoa at levels of 3–12% for unselected sperm [Rives et al, 2005; Moradkhani et al, 2006; Ogur et al, 2006]. Consequently, the vast majority of the disomy 13 and nullisomy 13 spermatozoa in the present study (in total 41.8%) ought to be derived from the rob(13;13) cell line (Table I).…”
Section: Discussionmentioning
confidence: 99%